PREDICTION OF AIRCRAFT NORMAL OVERLOAD EXTREME VALUE BASED ON PEARSON-Ⅲ DISTRIBUTION - LEI XiaoBo; WEN Min; LEI DiYuan; ZHANG XiaMei (Jixie qiangdu)
Based on Pearson-Ⅲ distribution（ P-Ⅲ） representing much capacity for fitting extreme value data,research on Nzextreme values were carried on. Calculation method on the deviation coefficients Φp of skew coefficients Cswas deduced and established,which eliminated look-up and interpolation errors. In consideration that there was not uniform quantitative judge standard on optional curving fitting when fitting real data by P-Ⅲ distribution on the curve-fitting method,Using the maximum membership principle judged curving fitting level according to fuzziness of flight data,and membership function was deduced in detail. Finally through calculation and analysis the conclusions were obtained: it’s scientific and rational that Nzextreme value was conformed with P-Ⅲ distribution from the aspects of mean relative error,maximum error and degree of membership between fitted values and real values,and that membership function seen as optimized objective function was more advantageous than curve-fitting method.